Epidemiology of Arterial Hypertension in Peru - Agusti C., Régulo (2006)
Objective: To determine arterial hypertension prevalence, knowledge, treatment, and control, in Peru. Design, setting, participants: Cross sectional survey application and blood pressure measurement performed in 26 cities in 18 year-old or over adult population, 10 cities in the coast, 12 in the mountains at different altitude (below and above 3 000 meters above sea level), and 4 in the jungle. Interventions: The study done between February and November 2004 considered valid 14 256 surveys. Blood pressure was obtained with the same standard equipment, and diagnosis followed the recommendations of the Joint National Committees Seventh Report. Results: Arterial hypertension prevalence was 23,7% (males, 13,4%; females, 10,3%). In the coast, the prevalence was 27,3%; in the mountains, 18,8% below 3 000 meters and 22,1% above 3 000 meters; in the jungle, 22,7%. After the fourth decade of life the possibility of developing hipertensión was higher in the coast than in the other regions of Peru. Diastolic hypertension was predominant above 3 000 meters. The study determined that 55% of the population did not know they had hypertension; from those under treatment, 45,1% were compensated; 82% received angiotensin converting enzyme I inhibitors. We speculate on hematocrit, vasodilation and hypervascularization theories. Conclusions: Hypertension prevalence was similar in the three Peruvian regions. The possibility of developing hypertension after the fourth decade of life was higher in the coast. Diastolic hypertension was predominant above 3 000 meters. Over one half of the population did not know they had hypertension; from those Ander treatment 45,1% were compensated; most of the patients received angiotensin converting enzyme I inhibitors.